PERAN MODEL PEMBELAJARAN KONFLIK INTELEKTUAL TERHADAP KECERDASAN INTERPERSONAL MAHASISWA - Sri Wahyuni; Rina Devianty (AWLADY : Jurnal Pendidikan Anak, 2019)
This paper presents the application of the intellectual conflict learning model in the context of the emotional development of children in the age of RA and their role in the interpersonal intelligence of students. This type of research is mixed methods. The tools used in this study are questionnaires, observational sheets and document studies. Analysis of the data used in this study: qualitative data analysis by Miles and Huberman and analysis of quantitative data using simple regression tests. The results showed that: (1) the application of the intellectual conflict learning model had an impact on the cognitive aspects of the emotional development of children, affective and psychomotor in the emotional development of RA children; and (2) the intellectual conflict learning model provides a positive role for the interpersonal intelligence of the students.